Análise crítica da gestão do lodo gerado em estações de tratamento de água – cenário brasileiro - Silva, Luana Ribeiro da; Achon, Cali Laguna; Isaac, Ricardo de Lima (International Workshop for Innovation in Safe Drinking Water, 2022)
The Brazilian National Solid Waste Policy, Federal Law 12.305/2010 establishes, in addition to the principles, objectives and instruments, some guidelines on the management of solid waste. Waste from sanitation public services is the residue generated in this activity. Therefore, the waste from Water Treatment Plant (WTP) must be managed in according to the principles of this law. The availability of data on the generation and destination of this waste is essential for defining strategies and decision making. This work aims to perform a critical analysis of the indicators on the management of WTP sludge in the Brazilian scenario. The results show that the largest data collection system on sanitation services in Brazil does not have indicators related to the topic.